Antimicrobial Efficacy and Synergy of Metal Ions against Enterococcus faecium, Klebsiella pneumoniae and Acinetobacter baumannii in Planktonic and Biofilm Phenotypes - Vaidya, Misha Y.; McBain, Andrew J.; Butler, Jonathan A.; Banks, Craig E.; Whitehead, Kathryn A. (Scientific reports, 2017)
The effects of metal ion solutions (silver, copper, platinum, gold and palladium) were determined individually and in combination against Enterococcus faecium, Acinetobacter baumannii and Klebsiella pneumoniae . Platinum, gold and palladium showed the greatest antimicrobial efficacy in zone of inhibition (ZoI) assays. When tested in combinations using ZoI assays, gold/platinum, gold/palladium and platinum/palladium were indicative of synergy. Microbial inhibitory concentration demonstrated platinum and gold against Enterococcus faecium , platinum against Klebsiella pneumoniae and platinum and silver against Acinetobacter baumannii were optimal. Minimal bactericidal concentrations determined the greatest bactericidal activity was again platinum gold and palladium against all three bacteria. Fractional Inhibitory Concentration (FIC) studies demonstrated that the silver/platinum combination against Enterococcus faecium , and silver/copper combination against Acinetobacter baumannii demonstrated antimicrobial synergy. Following crystal violet biofilm assays for single metal ion solutions, antimicrobial efficacies were demonstrated for all the metals against all the bacteria Synergistic assays against biofilms demonstrated gold/palladium, gold/platinumand platinum/palladium resulted in the greatest antimicrobial efficacy. Overall, platinum, palladium and gold metal ion solutions in individual use or combination demonstrated the greatest antimicrobial efficacies against planktonic or biofilm bacteria. This work demonstrates the potential for using a range of metal ions, as biocidal formulations against both planktonic or biofilm bacteria.